Evaluating Total Mercury and Methyl Mercury Contents in Canned Tuna Fish of the Persian Gulf - Bashiri Dezfouli, Ali (Iran J Pharm Res, 2018)
Due to hygienic risks of mercury residues in food and marine originated supplements, measuring total mercury and methyl mercury contents of canned tuna as a highly consumable marine food product is essential. In this study, 40 canned Tuna fish (from Persian Gulf) were collected in 2015 and then flame atomic absorption spectrometer (FAAS) and thermo gas chromatography mass spectrophotometry were used to measure total mercury and methyl mercury, respectively. The results indicated that the average contents of total mercury and methyl mercury of the canned tunas, with 34.2 and 29.5 ppb decrements compared with 2009’s measurement, were 177.4 and 143.7 ppb respectively. The highest concentration of the total mercury was 315.2 while it was 267.9 ppb for methyl mercury. This study showed that the content of the mercury in canned tunas of the Persian Gulf was less than the Maximum Residue Limit (MRL).